Glycated hemoglobin as a predictor for gestational diabetes - Rania Mostafa Emam; Aziza H Nassef; Hanaa Abou-Raia (Wolters Kluwer Medknow Publications, 2021)
Background Gestational diabetes mellitus (GDM) may cause fetomaternal complications. GDM can be diagnosed conventionally by an oral glucose tolerance test (OGTT). Glycated hemoglobin (HbA1c) is a marker for the blood glucose level in the previous 2-3 months. Objective The aim was to assess the role of using HbA1c as a predictor for developing gestational diabetes in the second trimester. Patients and methods Fifty pregnant women were investigated by ultrasound, and HbA1c and OGTT were performed for all cases at 18-22 weeks of gestation and repeated at 32-36 weeks of gestation. Results There were statistically significant differences between women with HbA1c value less than 5.7% and those with 5.7-6.4% according to BMI, parity, and maternal weight. A positive correlation was detected between HbA1c level and development of GDM according to OGTT, which was done in the third trimester, as women with HbA1c values less than 5.7% have decreased risks of developing GDM than women with higher levels of HbA1c. Follow-up of all cases detected significant relation between level of HbA1c and neonatal birth weight, neonatal ICU admission, and APGAR score, where the pregnant women whose HbA1c less than 5.7% got infant with less birth weight and better APGAR score and the incidence of neonatal ICU admission was less in their infants. Conclusion HbA1c can be used to predict the development of GDM in second trimester. Receiver operating characteristic curve identified that the best cutoff value of HbA1c was 5.2%, with sensitivity of 75%, specificity of 80%, positive predictive value of 71.4%, negative predictive value of 82.8%, with accuracy of 87.2% for diagnosing GDM.